Nursing Students’ Perceptions of Lesbian, Gay, Bisexual and Transgender Behavior - Rahmawati, Nur Rini; Sriati, Aat; Yulianita, Henny (Journal of Nursing Care, 2024)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a deviant behavior that is not in accordance with the norms in society. Nursing students as prospective nurses will deal with a variety of patients including LGBT patients so it is necessary to have a negative perception of LGBT that does not justify LGBT but does not counter LGBT excessively which triggers the tendency to behave discriminatory towards LGBT. The purpose of this study was to determine the perception of nursing students about LGBT. The research method used was descriptive quantitative with propotionate stratified random sampling technique on a sample of 302 nursing students from 2019 to 2022. The instrument used was the perception of LGBT questionnaire with the validity test value of the calculated r value (0.30-0.67) ≥ r table (0.23) and the reliability test value of the Cronbach Alpha coefficient ≥ 0.632 with the result of 0.819. Data analysis using univariate techniques. The results showed 54.6% of students had a very negative perception and 0.3% were very positive. This means that most respondents view LGBT as a health problems and deviation. It is expected that the faculty and religious organizations on campus can provide a lot of information and adequate materials about LGBT.Keywords: LGBT, Perception, higher Students education